Risk factors and consequences of conversion in laparoscopic major liver resection. (2nd April 2015) - Cauchy, F; Fuks, D; Nomi, T; Schwarz, L; Barbier, L; Dokmak, S; Scatton, O; Belghiti, J; Soubrane, O; Gayet, B
Abstract: Background: Although recent reports have suggested potential benefits of the laparoscopic approach in patients requiring major hepatectomy, it remains unclear whether conversion to open surgery could offset these advantages. This study aimed to determine the risk factors for and postoperative consequences of conversion in patients undergoing laparoscopic major hepatectomy (LMH). Methods: Data for all patients undergoing LMH between 2000 and 2013 at two tertiary referral centres were reviewed retrospectively. Risk factors for conversion were determined using multivariable analysis. After propensity score matching, the outcomes of patients who underwent conversion were compared with those of matched patients undergoing laparoscopic hepatectomy who did not have conversion, operated on at the same centres, and also with matched patients operated on at another tertiary centre during the same period by an open laparotomy approach. Results: Conversion was needed in 30 (13·5 per cent) of the 223 patients undergoing LMH. The most frequent reasons for conversion were bleeding and failure to progress, in 14 (47 per cent) and nine (30 per cent) patients respectively. On multivariable analysis, risk factors for conversion were patient age above 75 years (hazard ratio (HR) 7·72, 95 per cent c.i. 1·67 to 35·70; P = 0·009), diabetes (HR 4·51, 1·16 to 17·57; P = 0·030), body mass index (BMI) above 28 kg/m 2 (HR 6·41, 1·56 to 26·37; P = 0·010), tumour diameter greater than 10 cm (HR 8·91, 1·57 to 50·79; P = 0·014) and biliary reconstruction (HR 13·99, 1·82 to 238·13; P = 0·048). After propensity score matching, the complication rate in patients who had conversion was higher than in patients who did not (75 versus 47·3 per cent respectively; P = 0·038), but was not significantly different from the rate in patients treated by planned laparotomy (79 versus 67·9 per cent respectively; P = 0·438). Conclusion: Conversion during LMH should be anticipated in patients with raised BMI, large lesions and biliary reconstruction. Conversion does not lead to increased morbidity compared with planned laparotomy. Abstract : Conversion does not increase morbidity